Carbon Taxes or Emissions Trading Systems? : Instrument Choice and Design - Parry, Ian.; Black, Simon; Zhunussova, Karlygash (Washington, D.C. : International Monetary Fund, 2022)
Carbon pricing should be a central element of climate mitigation strategies, helping countries transition to 'net zero' greenhouse gas emissions over the next three decades. Policymakers considering introducing or scaling up carbon pricing face technical choices between carbon taxes and emissions trading systems (ETSs) and in their design. This includes administration, price levels, relation to other mitigation instruments, use of revenues to address efficiency and distributional objectives, supporting measures to address competitiveness concerns, extension to broader emissions sources, and coordination at the global level. Political economy considerations also affect the choice and design of instruments. This paper discusses such issues in the choice between and design of carbon taxes and ETSs, providing guidance, broader considerations, and quantitative analyses. Overall, carbon taxes have significant practical advantages over ETSs (especially for developing countries) due to ease of administration, price certainty to promote investment, the potential to raise significant revenues, and coverage of broader emissions sources-but ETSs can have significant political economy advantages.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Foreign Exchange; Informal Economy; Nonrenewable Resources and Conservation; Underground Econom